Evaluasi Model Perhitungan Tarif Dasar Kamar Rawat Inap Pasien Berdasar Metode Activity Based Costing Study Pada Rs Siloam Kebon Jeruk - Asyari; Padri Achyarsyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of this study tested the basic rate calculation method in inpatients at Siloam Kebon Jeruk Hospital comparing tariff pricing policies with the calculation of the base price at the base rate, so as to obtain an overview of which classes subsidize and subsidized classes, explaining in detail each cost grouped by the company based on patient activity.  The ABC method becomes a comparison in the breakdown of activity costs. The calculation of the basic rate of patient hospitalization costs in different classes was determined based on the details of the activity costs of the patient's activities. The amount of cost subsidies provided to Class III and Class II is derived from the income of class VviP, VIP and Suite Room patients. Fixed Costs and Variable Costs are calculated based on the grouping of costs according to the provisions of cost accounting theory. The difference in costs obtained between the provisions of the hospital and the ABC method is a subsidy for patients at Siloam Kebon Jeruk Hospital.